Leptomeningeal metastasis from large-cell neuroendocrine carcinoma of the cervix: a case report and literature review - Xu, Peng; Wang, Zhen-Jiang; Dang, Xin-Mei; Zhu, Bao-Yu; Zheng, Zhang-Cai (Frontiers in Oncology, 2026)
Leptomeningeal metastasis (LM) from neuroendocrine carcinoma of the cervix (NECC) is extremely rare, with only five cases reported in the literature. Immune checkpoint inhibitors (ICIs) have the standard first-line treatment for metastatic cervical carcinoma and have been reported to improve intracranial response and survival in several types of cancer. A 50-year-old woman initially received pelvic radiation and chemotherapy for cervical cancer. At 1 year later, she complained of left breast, supraclavicular, and retroperitoneal lymph node metastases. She received targeted and adjuvant chemotherapy. At 15 months after diagnosis, she received radiotherapy due to nasopharynx and supraclavicular lymph node metastasis as well as treatment with a bispecific antibody targeting PD-1 and CTLA-4, cadonilimab, combined with chemotherapy. At 20 months after diagnosis, she experienced a transient unconsciousness and severe headache, nausea, and vomiting. The cytological demonstration of malignant cells in the cerebrospinal fluid (CSF) confirmed the presence of leptomeningeal metastasis. The therapeutic regimen then consisted of intrathecal chemotherapy combined with oral temozolomide. The authors highlight the diagnosis and treatment of LM from NECC, providing a rare clinical scenario.